Electrical components part II [ capacitors, fuses, flashers, and coils (Electricity and electronics, 2006)
(Producer) Capacitors, fuses, fuse links, circuit breakers, flashers, coils, and other devices are discussed. Computer animation, component cutaways, and lab experiments are used to demonstrate how these basic components are constructed and how they operate